Penerapan Konsep Waterfront pada Penataan Kawasan Pantai Penimbangan di Kabupaten Buleleng-Bali - Permana, I Made Dwi; Rumawan Salain, Putu; Agusintadewi, Ni Ketut (Jurnal Arsitektur Universitas Udayana; Vol 9 No 02 (2021): Jurnal Arsitektur, Universitas UdayanaDO - 10.24843/jaunud.v9i02.66809, 2021)
Penimbangan Beach is a beach near Singaraja, Buleleng. Tourists love this beach due to its beautiful scenery and various types of recreational facilities. Regardless of its potential, Penimbangan Beach has many problems, especially problems concerning the environment and the condition and availability of recreational facilities. The planning of this coastal area is necessary to maintain the sustainability of the beach and to ensure tourists’ safety and comfort during their visit. The planning of Penimbangan Beach as a recreational waterfront is conducted by taking into account the potential of Penimbangan Beach as a recreation area on the beach. A waterfront has elements that can be applied to the landscape aspect and building aspect. The application to landscape aspects results in open space, promenade, bridges, and floating buildings. Meanwhile, the application to building aspects results in building orientation and the planning of building placement. The application of waterfront elements is expected to preserve the environment and provide comfort for visitors to Penimbangan Beach.  Keywords: planning, beach, recreational waterfront